2018
DOI: 10.1002/adma.201705644
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrenes as High‐Performance Cathode Materials for Aluminum Batteries

Abstract: The pressing need for low-cost and large-scale stationary storage of electricity has led to a new wave of research on novel batteries made entirely of components that have high natural abundances and are easy to manufacture. One example of such an anode-electrolyte-cathode architecture comprises metallic aluminum, AlCl :[EMIm]Cl (1-ethyl-3-methylimidazolium chloride) ionic liquid and graphite. Various forms of synthetic and natural graphite cathodes have been tested in recent years in this context. Here, a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
203
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 59 publications
(41 reference statements)
5
203
0
6
Order By: Relevance
“…After 100 cycles at 100 mAh g −1 , scanning electron microscopy (SEM) imaging did not reveal changes to the Al surface (Figure S5, Supporting Information). This concurs with previous claims of dendrite‐free operation of ACB in acidic AlCl 3 :[EMIm]Cl melts …”
Section: Resultssupporting
confidence: 93%
“…After 100 cycles at 100 mAh g −1 , scanning electron microscopy (SEM) imaging did not reveal changes to the Al surface (Figure S5, Supporting Information). This concurs with previous claims of dendrite‐free operation of ACB in acidic AlCl 3 :[EMIm]Cl melts …”
Section: Resultssupporting
confidence: 93%
“…AIBs comprise of a metallic aluminum that serves as the anode and the negative current collector, a chloroaluminate ionic liquid as the electrolyte with a AlCl 3 :EMImCl molar ratio (r)>1 (only in this cases reversible electrodeposition of metallic Al is possible), an Al‐insertion cathode material and a positive current collector. The vast majority of studies have been mainly focused on increasing energy density through the development of new cathode materials, e. g. vanadium oxides, metals sulfides, polymers, MXene, tellurium or graphitic materials amongst others . Most of these studies were carried out using expensive or unpractical materials like glassy carbon, molybdenum (Mo),, tungsten (W), or tantalum (Ta), due to the anodic dissolution of cheap and commonly used current collectors, e. g. Ni, Cu, Ti or stainless steel.…”
Section: Figurementioning
confidence: 99%
“…Therefore, it is necessary to develop a stable and sustainable current collector. Several research groups have suggested new current collectors ,. However, they can operate only above 0.5 V of the low cutoff voltage.…”
Section: Figurementioning
confidence: 99%